International Low Impact Development Conference 2018 2018
DOI: 10.1061/9780784481783.010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Analysis of Hydraulic Conductivity, Snow Depth, and Soil Properties of a Bioretention System

Abstract: Bioretention Cells (BC) are a Low Impact Development technology that provide distributed storm water management near to its source. Most research envisages BC as a black box with ambiguous processes between the input and the output. This thesis aims to consider BCs as heterogeneous systems with physical processes that vary both spatially and temporally. For this study, a 5-year-old BC at Kortright Centre for Conservation in Vaughan, Ontario is used as an investigation area. The following results were observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The volume of the bioretention cell was poorly utilized, with a low soil–water interfacial area of 21 m 2 /m 3 (calibrated from the rhodamine WT tracer, KGE = 0.76), high hydraulic conductivity of ∼44 cm/h, a low effective volume, and a poor hydraulic efficiency of 0.13. This poor utilization suggests that there were large dead volumes and an uneven distribution of the inflow inside the bioretention system, which is typical of the undersized systems or poorly designed or maintained bioretention cells.…”
Section: Resultsmentioning
confidence: 99%
“…The volume of the bioretention cell was poorly utilized, with a low soil–water interfacial area of 21 m 2 /m 3 (calibrated from the rhodamine WT tracer, KGE = 0.76), high hydraulic conductivity of ∼44 cm/h, a low effective volume, and a poor hydraulic efficiency of 0.13. This poor utilization suggests that there were large dead volumes and an uneven distribution of the inflow inside the bioretention system, which is typical of the undersized systems or poorly designed or maintained bioretention cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly Asleson et al (2009) observed low KSat values near the inlet, but also distributed randomly throughout the cell. Also, in Gnanaraj (2018) study of the KV site also used in this study, KSat was higher in the centerline of flow and lower along the side slopes, but there was no strong correlation between KSat and distance away from the inlet. In a tracer test also at the KV site, only 30% of the soil volume was used (Gu et al In Prep.…”
Section: Monitoring and Maintenance Requirementsmentioning
confidence: 58%
“…The formulas for converting between the rate of fall (cm/min) and KSat are described in detail in Elrick & Reynolds (1992). Guelph Permeameter measurements were taken in the centerline of flow, and not along the edges or sides of the bioretention systems, as Gnanaraj (2018) showed that this was where the lowest KSat values were measured. All KSat measurements were taken within a single day at a given site, and all sites were visited between May and July 2019, except for KV which had KSat testing performed in July 2017.…”
Section: Infiltration Capacity Testingmentioning
confidence: 99%